Density Functional Study of the Adsorption of Methanol and its Derivatives on Boron Nitride Nanotubes - Ali Ahmadi Peyghan; Maziar Noei (Adsorption Science & Technology)
Changes in the structural and electronic properties of chemically modified boron nitride nanotubes (BNNTs) using methanol and its derivatives including CH 3 CH 2 CH 2 OH CH 3 CH 2 OH, (ph)CH 2 CH 2 OH, CH 2 COOH and (CN)CH 2 CH 2 OH were investigated using density functional theory calculations. The study results showed that molecules of methanol can be chemically adsorbed on top of a sidewall B atom with an adsorption energy of −0.67 eV, which is stronger than that of carbon nanotubes. When using different derivatives of methanol, the adsorption energies and charge transfer from the adsorbate to the BNNT depending on the electron-withdrawing or electron-donating capability of the subgroups within the derivatives. Subgroups with strong electron-withdrawing capability generally lead to transfer less charge and smaller adsorption energy. The calculated density of state shows that the electronic properties of the BNNT are only slightly changed by the chemical modification. However, preservation of the electronic properties of BNNTs coupled with the enhanced solubility suggests that chemical modification of BNNTs with either methanol or its derivatives may be an effective way for purification of the BNNTs.